The difference in hand hygiene compliance rate between unit-based observers and trained observers for World Health Organization checklist and optimal hand hygiene. (January 2020) - Baek, Eun-Hwa; Kim, Se-Eun; Kim, Da-Hye; Cho, Oh-Hyun; Hong, Sun In; Kim, Sunjoo
Highlights: There was a small disparity in the World Health Organization checklist compliance rate for hand hygiene (HH). However, there was a large gap of disparity in the optimal HH compliance rate. The optimal HH rate was low especially for the physicians and before the clean and aseptic procedure. Abstract: Background: Hand hygiene (HH) is crucial to prevent healthcare-associated infections and the spread of multidrug-resistant organisms. The monitoring of HH compliance may be affected by observer expertise. A sufficient duration of HH is necessary to remove microorganisms. The aim of this study was to measure compliance with both the World Health Organization (WHO) checklist and optimal HH as reported by unit-based observers and infection control nurses (ICN). Methods: Optimal HH was defined as adhering to the exact duration and following a six-step procedure. The disparity in compliance with the WHO checklist and optimal HH was analyzed among each profession, unit, and indication, covering a period of 3 years. Results: There was a statistically significant difference in WHO checklist compliance (94.4% vs. 87.0%, p  < 0.01) and optimal HH rate (86.3% vs. 42.4%, p  < 0.01) between unit-based observers and ICN. The optimal HH rate was especially lower for doctors (30.1%), in the intensive care units (39.4%), and before clean and aseptic procedures (37.0%) as observed by ICN. Conclusions: Although the overall WHO checklist HH rate was reported to be higher than 90%, optimal HH was only half this rate. More education and awareness of the significance of HH, as well as adherence to the optimal HH procedures, are needed to prevent hospital-acquired infections.